2021
DOI: 10.37506/mlu.v21i1.2335
|View full text |Cite
|
Sign up to set email alerts
|

Education as Predictor of Low Birth Weight among Female Worker in Indonesia

Abstract: Female workers are a vulnerable group in Indonesia because in addition to working to help their husbands earn a living, they also still have to be responsible for domestic affairs. This study aimed to analyze the effect of the level of education on the incidence of LBW in female workers in Indonesia. The analysis uses the 2017 Indonesian Demographic and Health Survey data. Stratification and multistage random sampling method get 18,061 female workers as respondents. The final stage was done using binary logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Research in Brazil showed a significant decrease in LBW neonates born to higher-education mothers, and a slight rise in mothers with poor education was reported [37]. These results align with previous studies in various countries, stating that better mothers' education level was a protective factor for LBW cases [12,19,38].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Research in Brazil showed a significant decrease in LBW neonates born to higher-education mothers, and a slight rise in mothers with poor education was reported [37]. These results align with previous studies in various countries, stating that better mothers' education level was a protective factor for LBW cases [12,19,38].…”
Section: Discussionsupporting
confidence: 87%
“…LBW defines maternal health problems, maternal malnutrition, sporadic access to ANC facilities, and the low socioeconomic status of mothers in general [10]. Several studies have explained that parental, nutrition, educational, medical, environmental, and socio-cultural factors cause LBW [6,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A study in South-east Nigeria informed that the main reasons cited by people who do not want to participate in health insurance mechanisms are a poor understanding of how the health care system works and a lack of a steady source of income [18]. Generally, several previous studies have informed that better education levels are positively related to program performance output in the health sector [28][29][30][31][32]. On the other hand, lower education levels are a barrier to achieving better performance in the health sector [33,34].…”
Section: Discussionmentioning
confidence: 99%